The development of the human development index and its sub-indicators in Syria during the period (2010-2020) - سليمان, حيان; مجد نعامة, (Latakia University Journal -Biological Sciences Series, 2023)
The research aimed to measure the human development index and its sub-indicators and its development in Syria during the period (2010-2021), and to identify the factors most affecting the value of the index (education, health, income) The research was carried out at the level of the Syrian Arab Republic, relying on World Bank statistics for indicators of life expectancy at birth, literacy rate, gross school enrollment ratio, and per capita GDP during the period (2010-2020), In this research, the descriptive analytical approach was relied upon in studying and calculating the human development index at the level of the Syrian Arab Republic using tables, arithmetic averages, mathematical equations, and estimating the correlation coefficient (Pearson) and its significance between the human development index and its related sub-indicators (health, education, and income), in addition to calculating the coefficient Determination to calculate the relative importance of the sub-indicators in determining the value of the human development index during the studied period. The results of the research showed that Syria falls within the middle level according to the life expectancy at birth and the learning index during (2010-2020), on the other hand, it came in the low level according to the gross domestic product index according to purchasing power parity (at current prices in international dollars), and it occupied a medium level according to Human development index during the studied period, based on the classification of the United Nations Development Program,The results of the research indicated that there is no statistically significant relationship between the two indicators (life expectancy at birth and gross domestic product) and the human development index. The results also indicated the existence of a statistically significant relationship between the learning index and the human development index in Syria during the period studied,The results also indicated the high relative importance of the learning index in determining the value of the human development index (65%) in Syria during the studied period, compared to (17)% for the life expectancy index at birth and (0.2)% for the income index.